(3GdeRL Hjf GdfXGe GdQFGSj hGdfXGe GdHQdeGfj hBKGQg (B/ s - (3edGc QGLj GScfOQs; (3hgjH YjGO SdGeIs; (3LGeYI CSjhWs (3cdjI GdMbhbs ((3CSjhW (B: s (3cdjI GdMbhb (B- (3LGeYI CSjhWs, 2004)
(3HXghQ eHOG GdaUd Hjf GdSdWGJ fTGJ GfXeI Mce eNJdaI efgG eG GNP HGSdhH GdaUd GdeWdb Hjf GdSdWJjf GdJTQjYjI h GdJfajPjI h gh GdfXGe GdQFGSi h efgG eG GNP HGSdhH GdaUd GdeQf Hjf GdSdWJjf BfaJi GdHjGf hgh GdfXGe GdHQdeGfi h GNjQG GdfXGe GdeMGSHi y fXGe McheI GdLeYjIy GdPi jbhe Ydi GSGS acQI hMOI GdSjGOI h JQcjRgG ai jO GdeLdS GdfjGHi HeYfi GNQ gjefg GdSdWI GdJTQjYjI Ydi GdSdWI GdJfajPjI (B. (3GYJeOJ NWI GdHMK Ydi JNUjU aUd JegjOi dHjGf eOdhd GdeUWdMGJ GdeSJNOeI ceG Je GjQGO eaghe Gdabg dcd ef GdfXGejf GdQFGSi h GdHQdeGfi GeG HGdfSHI dHjGf eOdhd GdeRL HjfgeG GcJai Gdabg HeLQO GdGTGQI Gdi GdeRL Hjf GdfXGejf ShGA Ydi GdUYjO GdaQfSi GdMGdi Gh GdeUQi GHGf OSGJjQ eG HYO KhQI (B23 (3jhdjh (B1952 (3Ohf eMGhdI UjGZI eaghe dg h jQLY Pdc ai JbOjQfG Gdi UYhHI gPG GdJMOjO fXQG dGf eOi GdeRL Hjf YfGUQ cd ef GdfXGejf SGdai GdHjGf jJaGhJ ef OSJhQ dGNQ ai GdOhdI GdhGMOI (B: (3ceG jNJda ef OSJhQ OhdI dGNQi(B. (3hai eMGhdI ef LGfHfG dJPdjd Jdc GdUYhHI MQUfG Ydi JbOje JYQja ddeRL Hjf GdfXGejf GdQFGSi h GdHQdeGfi Mjf YQafGg HGfg GSdhH jbhe Ydi GdNdW Hjf HYV YfGUQ cd ef GdfXGejf GdQFGSi h GdHQdeGfi HcjajI ef TGfgG JQLjM caI GdSdWI GdJfajPjI Ydi caI GdSdWI GdJTQjYjI hbjGe YdGbI JYGhf h QbGHI eJHGOdI HjfgeG(B.s
(3QSGFd fSNI efaQOIs
(3GWQhMI (B((3OcJhQGI(B) - (3LGeYI CSjhW, cdjI GdMbhb, bSe GdbGfhf GdOSJhQj(B,s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 287-305 (3UaMIs
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdfXGe GdQFGSj (B-s -- (3eUQ(B.s; (3GdHQdeGf(B.s -- qrmak; (3GdSdWGJ GdKdGK(B.s -- qrmak; (3GdfXGe GdQFGSjs; (3GdfXGe GdHQdeGfjs; (3GdeRL s; (3KfGFjI GdLgGR GdJfajPjs; (3eLdS GdhRQGAs; (3eLdS GdTjhNs; (3GdMQjGJ GdYGeIs; (3MGdg GdWhGQFs; (3MGdg GdGSJYLGds; (3QSGFd LGeYjIs -- (3LGeYI CSjhWs -- (3GdbGfhf GdYGes